Research on the urban climate of Toruń by the Department of Meteorology and Climatology of UMK: an overview of history and results - Przybylak, Rajmund; Uscka-Kowalkowska, Joanna (Acta Geographica Lodziensia, 2019)
The article presents the history of research into the urban climate of Toruń initiated and conducted by the Department of Meteorology and Climatology of Nicolaus Copernicus University. Two periods of intensive research on the subject were identified: 1981–1993 and 2011–present. In the first period, measurements were taken at a significantly smaller number of points and covered a narrower scope than in the second period. The measuring equipment was also significantly different, with mercury thermometers and drum recorders (thermohygrographs) being used in the first period, and automatic meteorological stations in the second. Results from both periods, specifically from 1982 and 2012, confirmed the existence of an urban heat island (UHI) and significant differences in the spatial distribution of air humidity. In both analysed periods, differences in mean annual temperature and air humidity between the city centre and the reference station were about 1°C and 7%, respectively. The lack of changes in UHI intensity and spatial distribution of air humidity between the analysed years can be explained by the lack of significant changes in the development of Toruń’s Old Town.